+0  
 
0
80
1
avatar

I'm not sure how to approach this problem. So far I thought about multiplying the 2 by the other 2. Some assistance would be appreciated.

2(x)^3-2n 2(1/x)^2n = 4(1/x)^n+3

 Jun 12, 2021
edited by Guest  Jun 12, 2021
 #1
avatar+287 
+1

2(x)^3-2n 2(1/x)^2n = 4(1/x)^n+3 

 

  2(x)(3-2n)  * 2(x)-2n  = 4(x)-(n+3)     **multiply on the left side to make 4(x)m+n

                                                           

 4(x)(3-2n-2n)     =  4(x)-(n+3)    

 

3-4n = -n-3

-3n = -6

I think, you can see the whole picture now.

 Jun 12, 2021
edited by Bginner  Jun 12, 2021

30 Online Users

avatar
avatar